Diagnostic classification of irritability and oppositionality in youth: a global field study comparing ICD‐11 with ICD‐10 and DSM‐5. (12th May 2020) - Evans, Spencer C.; Roberts, Michael C.; Keeley, Jared W.; Rebello, Tahilia J.; de la Peña, Francisco; Lochman, John E.; Burke, Jeffrey D.; Fite, Paula J.; Ezpeleta, Lourdes; Matthys, Walter; Youngstrom, Eric A.; Matsumoto, Chihiro; et al.
Abstract : Background: Severe irritability has become an important topic in child and adolescent mental health. Based on the available evidence and on public health considerations, WHO classified chronic irritability within oppositional defiant disorder (ODD) in ICD‐11, a solution markedly different from DSM‐5's (i.e. the new childhood mood diagnosis, disruptive mood dysregulation disorder [DMDD]) and from ICD‐10's (i.e. ODD as one of several conduct disorders without attention to irritability). In this study, we tested the accuracy with which a global, multilingual, multidisciplinary sample of clinicians were able to use the ICD‐11 classification of chronic irritability and oppositionality as compared to the ICD‐10 and DSM‐5 approaches. Methods: Clinicians ( N  = 196) from 48 countries participated in an Internet‐based field study in English, Spanish, or Japanese and were randomized to review and use one of the three diagnostic systems. Through experimental manipulation of validated clinical vignettes, we evaluated how well clinicians in each condition could identify chronic irritability versus nonirritable oppositionality, episodic bipolar disorder, dysthymic depression, and normative irritability. Results: Compared to ICD‐10 and DSM‐5, ICD‐11 led to more accurate identification of severe irritability and better differentiation from boundary presentations. Participants using DSM‐5 largely failed to apply the DMDD diagnosis when it was appropriate, and they more often applied psychopathological diagnoses to developmentally normative irritability. Conclusions: The formulation of irritability and oppositionality put forth in ICD‐11 shows evidence of clinical utility, supporting accurate diagnosis. Global mental health clinicians can readily identify ODD both with and without chronic irritability.